Zionisme dan Identitas Keyahudian : Telaah Ashabiyyah Ibnu Khaldun - Utama, Mohamad Rezky (Journal of Integrative International Relations, 2021)
Zionism is a form of Jewish nationalism that is related with the Jewish identity and the spirit of nationalism between Jews. The concept of identity by Patricia Goff and Kevin Dunn, along with the main theory of ashabiyyah from Ibn Khaldun, are used in this research to analyze and ezplain Zionism as an identity uniting factor among European Jews. Zionist ideology started from the sense of same experience amongst European Jews who started to look for their identity in the middle of anti-Semitism in Europe. Moreover, this ideology become the uniting factor amongst Jews to have their own state and their own land. The wars and conflicts that was happened along the way of the establishment of Israel until it had been established strengthened the Jewish identity that was initiated by Zionists in Israel. And this research found out that Zionism will not disappear in immediate future.